Policy change and farmer feedback: Does anonymity matter? Evidence from Uzbekistan - Liutin, Anton; Dower, Paul Castañeda; Alvi, Muzna (International Food Policy Research Institute, 2025)
Policymakers in countries that are transitioning away from authoritarian regimes can face challenges in obtaining unbiased information about local conditions—as do researchers and international community representatives working in these countries, including those trying to understand policy change. This information problem is a critical challenge for water security.